ANALISIS PENGARUH FAKTOR PRODUKTIVITAS TENAGA KERJA DI KABUPATEN DAIRI, PROVINSI SUMATERA UTARA 1993-2003 - Dionisius Sihombing (Research Centre for Population, Indonesian Institute of Sciences, 2009)
Workforce is one important factor in an economic activity. The low quality of labour will affect the quality is getting. Productivity is the ability of labour in producing one unit of output within a certain time. Labour productivity is one indicator of employment that can deliver economic growth. In the economic sector, productivity magnitude can be obtained through the magnitude of economic growth described by the GDP. Labour productivity is measured by the size of GDP per labour in an economic activity. This research was carried out in Dairi Regency, aiming to determine changes in labour productivity is caused by education and health factors. This study uses the statistical data is secondary data during the period 199 3-2003, with the method of multiple regression analysis approach used method of least squares (OLS) regression method in relation to two variables. Results obtained where education and health factors influence for 77.19% of the change in labour productivity. Local governments should make efforts in improving the serious education and health in order to achieve high productivity.Keywords: Education, Health, Labor productivity.